From Farm to Community: Evaluating Social Sustainability in Organic Vegetable-Picking Tourism, Malang City - Sulistyan, Riza Bahtiar; Aulia, Vemy Martha; Solikah (Badan Perencanaan Pembangunan Kota Malang, 2025)
Community-based agrotourism is increasingly recognized as a driver of local empowerment, yet its social sustainability dimensions remain underexplored in Southeast Asia. This study evaluates social sustainability at an organic vegetable-picking tourism site in Malang City using eleven indicators derived from the literature: availability, accessibility, connectivity, density, diversity, legibility, safety, versatility, participation, social actions, and equity. Field observations and semi-structured interviews with managers, community members, and visitors revealed strong performance in local participation, diversity of activities, and educational value creation. However, challenges remain in public transport accessibility, digital wayfinding, formalizing collaborations with nearby businesses, and managing peak-period congestion. This study contributes to the literature by operationalizing a multidimensional framework for social sustainability in a peri-urban agrotourism setting and offers practical recommendations to strengthen inclusivity, visitor flow management, and community linkages. The findings demonstrate how such initiatives can advance SDG 11 (Sustainable Cities and Communities) and SDG 12 (Responsible Consumption and Production) by integrating tourism development with local social objectives.